Nozokomiyal Enterococcus faecium Meninjiti: Olgu Sunumu - Eroğlu, Cafer; Aydoğan, Seyhan; Pekbay, Ayhan (My University, 2003)
Tip II diyabetli 66 yaşındaki kadın hastada nozokomiyal enterokok (Enterococcus faecium) meninjiti saptandı. Hasta nozokomiyal enterokok infeksiyonlarını kolaylaştıran altta yatan ciddi hastalık (diyabetik nefropatiye bağlı böbrek yetmezliği), hastanede uzun kalış, santral kateter takılması, immünsüpresyon (diyabete bağlı) ve uzun süredir üçüncü jenerasyon sefalosporın tedavisi alma gibi risk faktörlerini taşımaktaydı. Rutin beyin-omurilik sıvısı (BOS) kültüründen bakteri üretilemezken, sadece kan kültürü şişesine ekilen BOS'nda bakteri üretildi. Uygun tedaviye karşın hasta yatışının 40. gününde kaybedildi. Sonuç olarak, hastane kaynaklı meninjitlerde enterokoklarda akla getirilmeli ve kültür pozitifliği belirleninceye kadar uygun ampirik tedavi verilmelidir.

Nosocomial enterococcal (Enterococcus faecium) meningitis was diagnosed in 66-year-old female patient with diabetes mellitus type II. This infection was facilitated by particular predisposing conditions, such as serious illness (renal insufficiency due to diabetic nephropathy), long hospitalization period, central catheter placement, immunocompromise (due to diabetes mellitus) and long term use of third generation cephalosporins. No bacteria could be isolated in routine media used for the culture of cerebrospinal fluid, but the agent could be isolated in CSF inoculated in hémoculture medium bottle. Unfortunately the patient died on the 40th day of hospitalization although she had received appropriate antibiotic therapy. In conclusion, enterococci should be considered in nosocomial meningitis, and appropriate empirical therapy should be given until culture results are obtained.
A case of nosocomial enterococcus faecium meningitis: Case report
Keywords: Enfeksiyon Hastalıkları